PENGARUH KERAGAMAN PRODUK DAN E-SERVICE QUALITY TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN (Studi pada Mahasiswa Universitas Diponegoro Pelanggan Zalora) - Adila Rainy; Widayanto Widayanto (Universitas Diponegoro, 2020)
Information technology in the era of globalization as it has now developed rapidly. The development of the use of the internet encourages the development of business so that the online trading transactions increases. Zalora is a fashion site that has a lot of market share in Indonesia, which was launched at the end of 2011. Zalora has a collection of more than 500 local, international and designer brands. Zalora customers can shop online with a choice of fashion products ranging from clothing, shoes, and accessories. Zalora is the largest online fashion business in Southeast Asia. The objective of this research is to investigate the direct effect of Product Diversity and E-Service Quality on Repurchase Intention and the indirect effect of Product Diversity and E-Service Quality on Repurchase Intention through Customer Satisfaction among Zalora customers in Diponegoro University. Non Probability sampling with Purposive Sampling used as methodology research for this research. Samples collected as many as 100 respondents of Zalora customers that selected based on consideration. The study uses a Partial Least Square analysis technique, which is estimated with the WarpPLS 6.0 program. Based on the result of data analysis by using Warp PLS, it indicates that direct impact of the test result on the research models find out the positive and significant results. Indirect impact of that test result on the research models are also indicate the positive and significant results.Researcher give advice to Zalora based on the lowest recapitulation value given by respondents to the assessment indicators, such as: provide the stock on each size, model and color of the product, improve the Zalora site system that causes customer disruption or failure to transact, provide product photos, product descriptions and product size details accurately, and prioritizes the customer’s shopping experience to fulfill their expectations